Assessment of Patient Safety Culture Among Doctors, Nurses, and Midwives in a Public Hospital in Afghanistan - Jabarkhil AQ; Tabatabaee SS; Jamali J; Moghri J (Dove Medical Press, 2021)
Abdul Qahir Jabarkhil,1,2 Seyed Saeed Tabatabaee,1 Jamshid Jamali,1 Javad Moghri1 1Social Determinants of Health Research Center, Mashhad University of Medical Sciences, Mashhad, Iran; 2MoPH, Estiqlal Hospital, Kabul, AfghanistanCorrespondence: Javad MoghriSocial Determinants of Health Research Center, Mashhad University of Medical Sciences, Mashhad, IranEmail moghrij@mums.ac.irIntroduction: The first step to improve the safety of patients in hospitals is to evaluate safety culture. Therefore, the patient safety culture in doctors, nurses and midwives should be reviewed regularly. The aim of the study was to determine the current state of patient safety culture among physicians, nurses and midwives at the Estiqlal Hospital in Kabul to promote an effective safety culture.Methods: This cross-sectional descriptive study was conducted from January to March 2020 among doctors, nurses, and midwives at the Esteqlal Specialized Hospital in Kabul. In that study, the data were collected through a survey of hospital. Among the 267 employees invited to participate, 267 (100%) completed the surveys. Descriptive statistics have been used to adjust frequency distribution tables and inferential statistics to identify differences in variable relationships. The independent sample T-test and one-way ‘ANOVA ‘ were used to check variations between groups, and SPSS version 25 was used for data analysis.Results: The findings of this study have shown that organizational learning and non-punitive response to errors have had the highest and lowest scores. Eight out of 12 dimensions of patient safety culture scored lower. Four dimensions of patient safety culture scored the highest. Overall, patient safety culture dimensions were low and poor (44%). This means the patient safety culture at the hospital was poor.Conclusion: The safety culture of the patients at the hospital was inappropriate, particularly in the eight dimensions of the patient safety culture, immediate intervention was necessary. The study emphasizes the creation of a desirable organizational climate, the need for staff involvement in various levels of decision-making, the creation of a culture of error reporting and recognizing the causing factors, and promoting a patient safety culture.Keywords: patient safety, patient safety culture, medical error, HSOPSC questionnaire